TINJAUAN YURIDIS TERHADAP KEWARGANEGARAAN ANAK HASIL PERKAWINAN CAMPURAN TIDAK SAH - Abellya Manalu; Koesmoyo Ponco Aji; Alrin Tambunan (STKIP Subang, 2025)
This study examines the role of immigration in determining the citizenship status of children born outside a legally recognized mixed marriage between Indonesian citizens and foreign nationals. The problem arises because such children often face legal uncertainty regarding nationality, which can lead to the risk of statelessness and the loss of fundamental rights. The objective of this research is to analyze the application of citizenship principles, namely ius soli, ius sanguinis, and naturalization, as stipulated in Law Number 12 of 2006 on Indonesian Citizenship, as well as to evaluate the legal consequences that may arise. This research employs a normative juridical method with a qualitative approach, relying on statutory regulations, legal literature, and relevant case studies. The findings reveal that children born from illegitimate mixed marriages experience difficulties in obtaining official documents such as birth certificates and passports, limited access to education and health services, and restricted legal protection due to the ambiguity of their citizenship status. The role of immigration becomes crucial in providing legal certainty and safeguarding children’s rights through supervision, regulation, and facilitation in citizenship administration. Thus, immigration authorities are not only responsible for border control but also for ensuring that every child’s right to citizenship is protected in accordance with national and international legal standards. Keywords: Immigration, Citizenship, Child, Mixed Marriage, Statelessness